2013
DOI: 10.5539/ijbm.v8n7p46
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Firm Trust Production: Theoretical Perspectives

Abstract: Although inter-firm trust plays a crucial role in inter-firm relationships that involve uncertainty, limited research has devoted to make a full review on inter-firm trust. The objective of the study is to investigate the sources of inter-firm trust in order to give a basement for building inter-firm trust. Drawn from many disciplines such as relationship marketing, social exchange theory, management, etc., this study has built the conceptual model to facilitate trust between partners in inter-firm relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…If properly executed and if founded on a trusting and long-term relationship, supply chain collaboration indeed leads to better operational performance (Anbanandam et al, 2011;Hua et al, 2009) and to global competitive advantage (Jones et al, 2010;McDowell et al, 2013;Nguyen and Liem, 2013;Rascovic and Morec, 2013). Soosay et al (2008) reported that having collaborative relationship is important in inculcating a culture of continuous innovation.…”
Section: Supply Chain Collaboration and Trustmentioning
confidence: 99%
See 2 more Smart Citations
“…If properly executed and if founded on a trusting and long-term relationship, supply chain collaboration indeed leads to better operational performance (Anbanandam et al, 2011;Hua et al, 2009) and to global competitive advantage (Jones et al, 2010;McDowell et al, 2013;Nguyen and Liem, 2013;Rascovic and Morec, 2013). Soosay et al (2008) reported that having collaborative relationship is important in inculcating a culture of continuous innovation.…”
Section: Supply Chain Collaboration and Trustmentioning
confidence: 99%
“…This means that a high level of trust between parties in a supply chain engagement is not necessary for a collaborative planning and decision-making process, like a sales and operations planning (SOP), as this could be a process or a system initiated by management and needs to be followed by the various planning stakeholders. Second, other perspectives of trust, such as transactional trust (dependence, formalization, and control) (Mamad and Chahdi, 2013), contractual and competence trust (Jones et al, 2010), and institutional trust (the regional context where the buyer and sellers are located) (Vieira et al, 2013;Nguyen and Liem, 2013), could be associated with collaborative planning and decision making. Doney and Cannon (1997) and Gullet et al (2010) noted that the real test of the presence of trust in a company is the sharing of private and even proprietary information between the supply chain parties.…”
Section: Relationship Between Supply Chain Collaboration and Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study of trust may be categorized based on how trust is viewed and composed: as an individual characteristic, as partner characteristics, as an characteristic of interpersonal transaction, and as an institutional phenomenon (Bhattacharya et al, 1998;Doney & Cannon, 1997;Ganesan, 1994;Kwon & Suh, 2004;Moorman et al, 1993;Zucker, 1986). The others, on the other hand, found the way to build trust (Nguyen & Rose, 2009;Nguyen & Liem, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…3, No. 9 ISSN: 2222 Previous studies have amply demonstrated the significant relationship between trust and customer satisfaction and loyalty in the banking business (e.g., Beerli, Martin & Quantana, 2004;Ehiobucher & Kan, 2012;Kantsperger & Kunz, 2010;Ndubisi & Wah, 2005;Ndubisi, Wah & Ndubisi, 2007) and in non-banking business ( Caceres & Paparoidamis, 2007;Casielles, Alvarez & Martin, 2007;Chattananon & Trimetsoontorn, 2009;Hau & Ngo, 2012;Kiyani, Niazi, Rizbi & Khan, 2012;Morgan & Hunt,1994;Narteh, Agbemabiese, Kodua & Braimah, 2013;Nguyen & Liem, 2013). …”
Section: International Journal Of Academic Research In Business and Smentioning
confidence: 99%